Piezo-fiber multipattern scanner for endoscopy - Tekpinar, Miyase; Khayatzadeh, Ramin; Ferhanoglu, Onur (SPIE, 2019)
We present a two-dimensional piezoelectric fiber actuator and a novel actuation scheme to establish three different scan patterns with single device. The flexibility in choosing scan patterns offers multiple options for the operator to choose between improved uniformity, high frame-rate to image abrupt biological applications, or circular field-of-view to better image naturally cylindrical cavities (gastrointestinal tract, esophagus, etc.). The presented device is capable of achieving different scan patterns with a robust actuation scheme that demonstrated through first presenting its mechanical frequency behavior, then generating 256 pixel width or diameter raster, spiral, and Lissajous patterns at ≥ 20 frames-per-second.The presented device, along with the actuation strategy is a promising candidate for integration with miniaturized laser scanning devices towards clinical use.